Divergence in parturition timing and vegetation onset in a large herbivore—differences along a latitudinal gradient. (24th June 2020) - Neumann, Wiebke; Singh, Navinder J.; Stenbacka, Fredrik; Malmsten, Jonas; Wallin, Kjell; Ball, John P.; Ericsson, Göran
Abstract : In northern environments, the period of access to high-quality forage is limited, exerting strong selective pressure to optimize the timing of parturition. We analysed timing and variation in moose ( Alces alces ) parturition dates of 555 females at 18 study sites across 12° of latitude (56–68° N, 1350 km) in Sweden. We found evidence for a spatial match of parturition timing to vegetation onset, but no evidence that moose adjust parturition to vegetation onset in a given year. We found a breakpoint at 64° N. Despite adaptation across latitudes, temporal divergences occurred. Females below 64° N calved after vegetation onset and females above 64° N calved before. Here, parturition before vegetation onset might be a strategy to optimize forage utilization time with the very short growing season. Highly seasonal environments such as at higher latitudes may make it advantageous to adapt parturition towards long-term climatic patterns by matching the most favourable period. Given the direction of temporal divergence, our study suggests that climate change may have less of an impact on moose parturition at northern latitudes than southern latitudes.